Anatomic Femoral Tunnels in Posterior Cruciate Ligament Reconstruction: Inside-Out Versus Outside-In Drilling. (January 2013) - Tompkins, Marc; Keller, Thomas C.; Milewski, Matthew D.; Gaskin, Cree M.; Brockmeier, Stephen F.; Hart, Joseph M.; Miller, Mark D.
Background: During posterior cruciate ligament (PCL) reconstruction, the placement and orientation of the femoral tunnel is critical to postoperative PCL function. Purpose: To compare the ability of outside-in (OI) versus inside-out (IO) femoral tunnel drilling in placing the femoral tunnel aperture within the anatomic femoral footprint of the PCL, and to evaluate the orientation of the tunnels within the medial femoral condyle. Study Design: Controlled laboratory study. Methods: Ten matched pairs of cadaver knees were randomized such that within each pair, 1 knee underwent arthroscopic OI drilling and the other underwent IO drilling. All knees underwent computed tomography (CT) both pre- and postoperatively with a technique optimized for ligament evaluation (80 keV with maximum mAs). Commercially available third-party software was used to fuse the pre- and postoperative CT scans, allowing comparison of the PCL footprint to the drilled tunnel. The percentage of tunnel aperture contained within the native footprint, as well as the distance from the center of the tunnel aperture to the center of the footprint, were measured. In addition, the orientation of the tunnels in the coronal and axial planes was evaluated. Results: The OI technique placed 70.4% ± 23.7% of the tunnel within the native femoral footprint compared with 79.8% ± 16.7% for the IO technique ( P = .32). The OI technique placed the center of the femoral tunnel 4.9 ± 2.2 mm from the center of the native footprint compared to 5.3 ± 2.0 mm for the IO technique ( P = .65). The femoral tunnel angle in the coronal plane was 21.0° ± 9.9° for the OI technique and 37.0° ± 10.3° for the IO technique ( P = .002). The tunnel angle in the axial plane was 27.3° ± 4.8° for the OI technique and 39.1° ± 11.5° for the IO technique ( P = .01). Conclusion: This study demonstrates no difference in the ability of the OI and IO techniques to place the femoral tunnel within the PCL femoral footprint during PCL reconstruction. With the technique parameters used in this study, the IO technique created femoral tunnels with a more vertical and anterior orientation than the OI technique. Clinical Relevance: Either technique can be used to place the femoral tunnel within the anatomic footprint. Consideration should be given to tunnel orientation following each technique, and what effect it has on graft bending angles, as these characteristics may affect graft strain and, ultimately, graft failure. In this regard, the IO technique likely produces gentler graft bending angles.